El futuro de la educación [superior]. Una reflexión entre la doxa y la episteme - Ruiz Ruiz, Marcos Fernando (2013)
Discover how the future will be has traditionally been a task entrusted to wizards and soothsayers. However, men and women of science—through the prospective discipline and research in future scenarios—have also faced the problem from a particularly different way. The educational phenomenon—not being aware of this concern about tomorrow—also becomes the object of study to establish guidelines for relevant strategic planning and foresight. In the following paragraphs, we will address future studies related to higher education with a proposed approach to the ethodologies used and we will seek to identify the convergence of future scenarios. Finally, to offer a significant contribution, we will propose some general strategies that universities must consider anticipating future challenges and difficulties